APPARATO E METODO PER IL TRATTAMENTO DI SCORIE METALLURGICHE - ANSOLDI MARCO; SOLDI LAURA; PRIMAVERA ALESSANDRA (2014)
An apparatus for processing metallurgic slag, associated to a melting furnace (1 1) having at least a melting chamber (13) and a deslagging aperture (15) from which a stream of slag (12) exits toward a collection point below, comprises a tubular element (18) having an exit end, and pneumatic feed means (20), cooperating with at least a tank (21) containing inertization additives (22). The pneumatic feed means (20) cooperate with the tubular element (18) and with the tank (21) to transfer the inertization additives (22) from the tank (21) toward the outside of the exit end of said tubular element (18), where there is at least one exit nozzle (19, 119, 219), to project the inertization additives (22) into the stream of slag (12) with a desired kinetic energy.